Nurses' perceptions about the patient safety climate in Primary Health Care - Edinêis de Brito Guirardello; Mariana Véo Nery de Jesus; Lilian Ceroni Vieira; Henrique Ceretta Oliveira; Maria Silvia Teixeira Giacomasso Vergilio (Universidade de São Paulo, 2024)
Objective: to evaluate the patient safety climate in Primary Health Care from the perspective of nurses working in the services. Method: a quantitative and cross-sectional study conducted with 148 nurses from a municipality in the state of São Paulo. The Brazilian version of the Primary Care Safety Questionnaire Survey and personal, professional, and organizational performance variables (intention to stay at work, job satisfaction, care quality, and frequency of incidents) were used. Parametric and non-parametric comparison tests and Spearman's correlation coefficient were performed, considering a 5% significance level. Results: the safety climate was positive, varying from 4.52 to 5.33 and differing across districts for workload (p=0.0214) and leadership (p=0.0129). The safety climate professional variables and dimensions differed in relation to the frequency of incidents. Teamwork and safety and learning system were strongly correlated with job satisfaction and moderately with perceived care quality. Conclusion: teamwork and safety and learning system stood out for their positive correlations with job satisfaction and care quality. A positive safety climate favors the involvement of Primary Care nurses to develop improvement plans aligned with the National Patient Safety Program.